Constraints imposed by key-material resources on renewable energy development. (July 2021) - Klimenko, V.V.; Ratner, S.V.; Tereshin, A.G.
Abstract: To limit global warming well below 2 °C, or even 1.5 °C, a rapid transition toward renewable energies must occur within the next several decades. This study examines the problem of resource constraints in the development of clean energy and transportation technologies (namely wind turbines and batteries in electric vehicles) for different global energy-consumption scenarios. For this study, lithium and cobalt (demand from electric vehicles) and neodymium, praseodymium, and dysprosium (cumulative demand from electric vehicles and wind power) were considered as critical materials. The application of simple dynamic models allows for an integrated assessment, taking into account changes in energy demand, resource intensity of wind energy and electric vehicles, and exploration and recycling technologies. The obtained results show that, irrespective of the considered scenario or the method used for estimating rare-earth element reserves, the demand for neodymium and praseodymium remains within a maximum of 12%–14% of the total reserves even when the development in recycling technologies is not considered. Meanwhile, the demand for dysprosium is much more significant at 86% in the absence of recycling technologies. There are strong indicators that clean-energy development can be threatened by the shortage of cobalt and lithium by the middle of this century unless we achieve rapid progress in technologies related to their exploration and reuse. Highlights: The problem of key-material constraints for clean energy development is examined. World economy can face Li and Co shortage in the next three decades. Recycling technologies should be developed to overcome critical-material shortage. Nd and Pr demand will be 12%–14% of reserves by 2100, while that for Dy will be 86%.